Ergonomics study of musculoskeletal disorders in preventive maintenance of prime mover and work study in improvement of maintenance straddle carrier / Mazhar Mohd Kawi and Al Faisal Masri - Mohd Kawi, Mazhar; Masri, Al Faisal (2002)
One of the main objectives of the project is to determine and evaluate the level of ergonomics awareness in our industries. Therefore, the project was carried out at one of the leading Ports in Malaysia in January 2002 named as NORTHPORT (MALAYSIA) BERHAD. As the workers are the main subjects in this project, the checklist and the questionnaires were used as the tools in order to get the valuable data for us to do an analysis. By using statistical technique for social science or SPSS software for window, we can get the relationship between the dependents and independent variables consist in the questionnaires. The early chapter in this project is the introduction of the musculoskeletal disorders and the workplace factors that contribute to the musculoskeletal disorders. Then we will explain about the processes of work study at Straddle Carrier before we commence with the methodologies and analysis for this project. Finally, the conclusions and recommendations were made as a corrective and also for preventive action to eliminate and reduce the level of musculoskeletal disorders and increase the ergonomics awareness for the employees and employer and also improve downtime of the machines.